From molecule to conservation: DNA-based methods to overcome frontiers in the shark and ray fin trade - Domingues, Rodrigo Rodrigues; Bunholi, Ingrid Vasconcellos; Pinhal, Danillo [UNESP]; Antunes, Agostinho; Mendonça, Fernando Fernandes (Springer Nature, 2021)
Over the last years, many studies have reported the challenge of precisely identifying shark and ray species from the fin trade. In Asia, the high demand for shark fin soup has resulted in correspondingly high prices for fins. This, in turn, has caused overexploitation of elasmobranch populations worldwide. Fin processing can cause the loss of morphological characteristics; therefore, species-specific identification can be performed only by DNA analysis. Most studies have reported the presence of threatened and protected elasmobranchs in the Asian trade market, highlighting the failure of current management and conservation policies. Here, were discussed the evolution of DNA-based methods for elasmobranchs identification and presented new approaches toward overcoming the illegal shark and ray fin trade. Firstly, we argued that universal standardized DNA-based methods based on COI and NADH2 should be developed for the main species in international trade. In addition, high throughput sequencing (HTS) protocols should be developed and used to identify previously unknown species from highly processed food containing multiple ingredients, such as shark fin soup. Moreover, we highlight the importance of increasing the knowledge about population genetics data, providing an atlas of geographically distinct DNA polymorphic regions. Such genetic data will allow geographic traceability of shark and ray products exported to Asia in order to identify hotspots of finning practice, thereby providing a roadmap to indicate hotspots where effective law enforcement needs to be implemented. These approaches are also necessary to find those responsible for such illegal capture and promote effective fisheries management plans.
Keywords: Conservation; Elasmobranchs; Fisheries management; Genetic identification; Wildlife trade